Projeto BioquímicAtiva: uma forma de estimular a interdisciplinaridade e aplicabilidade no ensino de bioquímica por meio da arte - Porto, Valéria Araújo (Universidade Federal do Tocantins, 2023)
The discipline of biochemistry, one of the components of the curricular matrix of courses in the health area, is commonly reported by academics as being an abstract subject that is difficult to associate with professional practice. Thus, it is necessary to use complementary educational strategies that address such contents in a more applicable and palatable way to academics, thus arousing greater interest in the subject. In this sense, the present work aimed at the elaboration of biochemical educational materials with a more playful and applicable language, having interdisciplinarity and art as a mediating link in this process. The activities developed are part of the extension project named BioquímicAtiva, which is linked to the Federal University of Tocantins, and which has the participation of professors and academics from the Undergraduate courses in Nutrition, Journalism and Letters, as well as members external to this institution. For the production of materials, the topics to be worked on are first selected, taking into account their practical relevance, as well as affinity and curiosity of the academic for the subject. Afterwards, the academic begins to study the subject through scientific articles and textbooks, in addition to periodically presenting seminars to the group. The improvement of competences and general abilities for the formation of the Nutritionist professional, with regard to communication, takes place through the participation of academics in courses and activities related to scientific dissemination and writing, as well as from the discussion of documentaries, interviews and creativity podcasts. The educational materials are produced in the form of texts, containing illustrations and/or collages, being destined for the BioquímicAtiva blog, its Instagram, and/or to compose two biochemistry books in development, in which one of them is based on several everyday stories to explain biochemical contents, while the other approaches biochemistry through poetry. The process of building the book on poetic biochemistry counts with the collaboration of a poet and collagist, who offers poetry workshops to academics, as well as creates exclusive collages for the project, in order for them to dialogue with the poems to be written. For the blog, educational materials are produced in two ways: as a smaller and more objective text, or in the form of a larger and more descriptive text. The arts and illustrations for the smaller texts are produced by the nutrition academic himself or come from articles and books, while for the larger texts, all illustrations are created by the project illustrator. After the material is finalized, it is sent for scientific review, carried out by collaborating professors with expertise in the subject. Subsequently, the material goes for journalistic review before its publication. To date, two materials have been produced for the blog, five for Instagram, one for the biochemistry book on everyday stories and three poems for the book of biochemical poetry. In conclusion, it was possible to notice throughout the process of creation the materials, the important role that art and interdisciplinarity play in the teaching-learning process of biochemical contents